Kekuasaan dan Taktik Mempengaruhi Orang Lain Dalam Organisasi - Maria Merry Marianti (Business Administration Department - Universitas Katolik Parahyangan, 2011)
Power and Influence Tactics, always exist in any organization. To become an effectiveleader or manager, every leader needs to know both of them. This paper try to describethe meaning of power, sources of power, types of power, how to increase or decreasepower, coalition (power in group), and influence tactics usually used in an organiza-tion. The direction of influence tactics can be upward, lateral, or downward. Powercan be differentiated into soft and hard power. Using soft-power is more effectivethan hard-power. To become an effective leader, a wise leader would use soft-powerand avoid using hard-power.Keywords: power, influence tactics, effective leader